Readthrough activation of early adenovirus E1b gene transcription. - Maxfield, L F (1997)
In cells productively infected with adenovirus type 5, transcription is not terminated between the E1a gene and the adjacent downstream E1b gene. Insertion of the mouse beta(maj)-globin transcription termination sequence (GGT) into the E1a coding region dramatically reduces early, but not late, E1b expression (E. Falck-Pedersen, J. Logan, T. Shenk, and J. E. Darnell, Jr., Cell 40:897-905, 1985). In the study described herein, we showed that base substitution mutations in the globin DNA that specifically relieved transcription termination also restored early E1b promoter activity in cis, establishing that maximal early E1b expression requires readthrough transcription originating from the adjacent upstream gene. To identify potential targets of readthrough activation, a series of recombinant viruses with double mutations was constructed. Each double-mutant virus strain had the transcription termination sequences in the first exon of E1a and a deletion within the transcription control region of E1b. Early E1b expression from the double-mutant strains was more defective than that from strains containing either mutation alone, indicating that the deleted regions (positions -362 to -35) are not the target for readthrough activation. Two findings suggested that a cis-dominant property of early viral templates is important for readthrough activation. First, the early E1b defect caused by the GGT insertion was not complemented in trans by factors present in late-infected cells. Second, restoration of E1b transcription at late times occurred concurrently with viral DNA replication. Readthrough activation may help convert virion DNA into a transcriptionally competent template prior to DNA replication and late transcription.